Adjacency Matrix Implementation for Evaluation of Land Use City Consistency to Fuzzy AHP (Case: Didactic Lands School Gorgan City) - Alireza Khajehshahkoohi; Husayn Karimzadeh; Mojtaba Hoosin nejad (جغرافیا و پایداری محیط)
There are a lot of quantitative and qualitative factors about establishment and planning for facilities on cities. The effect of factors on facilities may be different and meantime, because of positive and negative autocorrelation efficacies of land uses, adjustment and non adjustment between city land uses, special factors for each of them apply in land use mosaics settings. This process is complicated for strong dependence between various city land use and impressments of beneficiaries and several factors in activity Land use city increase complexity of subject. On the other hand, collective nature of city activities and organic non deterministic extant in priorities and opinions of planners and necessity to use of various priorities and opinions of planners in this process have necessitated to use simultaneously collective make decision method and various tools for supporting to decision as Geographic Information System(GIS). Thus in present research has presented Fuzzy AHP Model and has evaluated city educational uses adjustment as for all effective factors in land use adjustments on basis of synthetic viewpoint Multi – Criteria Decision Models (AHP) and theory of Fuzzy. The results demonstrate that all high schools in Gorgan hold on a almost adjustment range (0.052-0.026) in view of adjustment to factors that studied in this research. The results also showed more prices and different levels of adjustments dedicate to Gorgan high schools uses and to efficiency of designed model for evaluation of city land use adjustment.